Occupancy rates of excavated cavities and nest boxes in managed boreal forest in relation to forest structure - Hanzelka Jan; Baroni Daniele; Laaksonen Toni (TAYLOR & FRANCIS AS, 2025)
Cavity nesting birds depend on the availability of tree cavities for breeding, but the structure of the surrounding environment may also impact cavity occupancy. Here we investigated the effects of forest structure on occupancy rates of excavated cavities and similar-size nest boxes by cavity nesters in managed southern boreal forests in Finland. We recorded the occupancy over five breeding seasons (2017-2021) and derived forest structure parameters from high-resolution thematic raster maps. We found a high occupancy rate in nest boxes (81%), but lower rates in natural cavities excavated in forest interior, forest edges and retention trees (42-46%). The analyzes focusing on Paridae only revealed that the occupancy rates in nest boxes were decreasing with increasing amounts of Norway spruce and deciduous tree foliage biomass, and tree height, but increasing with the proportion of Scots pine. In forest interior cavities, we found a negative effect of stand age but a positive effect of the proportion of spruce. We conclude that the benefits of nest boxes can be maximized by considering specific forest parameters when deploying them. In excavated cavities the occupancy rates are likely more dependent on the varying internal quality than on the forest structure.